Fracture Resistance of Retreated Roots Using Different Retreatment Systems - Er, Kursat; Tasdemir, Tamer; Siso, Seyda Herguner; Celik, Davut; Cora, Sabri (European Journal of Dentistry, 2011)
Objectives: This study was designed to evaluate the fracture resistance of retreated roots using different rotary retreatment systems. Methods: Forty eight freshly extracted human canine teeth with single straight root canals were instrumented sequentially increasing from size 30 to a size 55 using K-files whit a stepback technique. The teeth were randomly divided into three experimental and one control groups of 12 specimens each. The root canals were filled using cold lateral compaction of gutta-percha and AH Plus (Dentsply Detrey, Konstanz, Germany) sealer in experimental groups. Removal of gutta-percha was performed with the following devices and techniques: ProTaper Universal (Dentsply Maillefer, Ballaigues, Switzerland), R-Endo (Micro-Mega, Besançon, France), and Mtwo (Sweden & Martina, Padova, Italy) rotary retreatment systems. Control group specimens were only instrumented, not filled or retreated. The specimens were then mounted in copper rings, were filled with a self-curing polymethylmethacrylate resin, and the force required to cause vertical root fracture was measured using a universal testing device. The force of fracture of the roots was recorded and the results in the various groups were compared. Statistical analysis was accomplished by one-way ANOVA and a post hoc Tukey tests. Results: There were statistically significant differences between the control and experimental groups (P<.05). However, there were no significant differences among the experimental groups. Conclusions: Based on the results, all rotary retreatment techniques used in this in vitro study produced similar root weakness. (Eur J Dent 2011;5:387-392)
Keywords: Fracture resistance; Retreatment; Root fracture; Rotary instruments